Secondary glaucoma in dogs and cats - Oria, A. P. (2013)
Glaucoma is a syndrome that affects animals of different species and in different moments of his life, having variables causes in function of this presentation. It is an ophthalmic emergency that may develop irreversible vision damage as well as the patient's aesthetic presentation. Increased intraocular pressure, presence of engorged episcleral vessels, conjunctival hyperemia, pain, anterior uveitis, lens luxation and buftalmia are commonly clinical signs presented by dogs while in cats, signs are less expressive, noting mydriasis, mild ciliary injection and progressive buftalmia. For diagnosis are carried out three basic procedures: tonometry, gonioscopy and ophthalmoscopy. The treatment can establish with medical therapy with or without surgical intervention, however, at some point it will be necessary to perform enucleation or evisceration of the eye bulb.